Three-Dimensional Hydromechanical Modeling during Shearing by Nonuniform Crust Movement - Yuqing Zhao; You-Kuan Zhang; Xiuyu Liang (Geofluids)
Hydromechanical modeling of a geological formation under shearing by the nonuniform crust movement during 10000 years was carried out to investigate the solid stress and pore pressure coupling processes of the formation from the intact to the fractured or faulted. Two three-dimensional numerical models were built and velocities in opposite directions were applied on the boundaries to produce the shearing due to the nonuniform crust movement. The results show that the stress and pore pressure became more and more concentrated in and around the middle of the formation as time progresses. In Model I with no fault, stress and pore pressure are concentrated in the middle of the model during shearing; however, in Model II with a fault zone of weakened mechanical properties, they are more complex and concentrated along the sides of the fault zone and the magnitudes decreased. The distribution of stress determines pore pressure which in turn controls fluid flow. Fluid flow occurs in the middle in Model I but along the sides of the fault zone in Model II. The results of this study improve our understanding of the rock-fluid interaction processes affected by crustal movement and may guide practical investigations in geological formations.